The relationship between austerity and food insecurity in the UK: A systematic review. (March 2021) - Jenkins, Rosemary H.; Aliabadi, Shirin; Vamos, Eszter P.; Taylor-Robinson, David; Wickham, Sophie; Millett, Christopher; Laverty, Anthony A.
Abstract: Background: In 2010, the UK government implemented austerity measures, involving reductions to public spending and welfare reform. We aimed to systematically review the relationship of austerity policies with food insecurity including foodbank use in the UK. Methods: We undertook a narrative systematic review (CRD42020164508) and searched seven databases, grey literature, and reference lists through September 2020. Studies with austerity policies (including welfare reform) as exposure and food insecurity (including foodbank use as a proxy) as study outcome were included. We included quantitative longitudinal and cross-sectional studies. Two reviewers assessed eligibility, extracted data directly from studies, and undertook quality assessment. Findings: Eight studies were included: two individual-level studies totalling 4129 participants and six ecological studies. All suggested a relationship between austerity and increased food insecurity. Two studies found that austerity policies were associated with increased food insecurity in European countries including the UK. Six studies found that the welfare reform aspect of UK austerity policies was associated with increased food insecurity and foodbank use. Sanctions involving delays to benefits as a response to a claimant not actively seeking work may increase food insecurity, with studies finding that increases of 100 sanctions per 100, 000 people may have led to increases of between 2 and 36 food parcels per 100, 000 population. Interpretation: UK austerity policies were consistently linked to food insecurity and foodbank use. Policymakers should consider impacts of austerity on food insecurity when considering how to reduce budget deficits. Funding: NIHR School for Public Health Research.